Hubungan Usia dan Masa Kerja Dengan Kelelahan Kerja Pada Pekerja Di HAR 1 dan HAR 2 PLTGU PLN Nusantara Power UP Belawan - Wasiyem, Wasiyem; Panggabean, Diani Sari; Rahayu, Pivit; Simanjuntak, Annisa Salsabila; Purba, Dwi Syahputri; Triana, Meutia Hafni Indah; Panjaitan, Wiranti Utami (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Workers in the Maintenance (HAR) department of power plants are at high risk of fatigue at work due to exposure to high temperatures, noise, and heavy physical workloads. Work-related fatigue can lead to decreased work effectiveness and increase the likelihood of accidents in the workplace. This study aims to analyze the relationship between age and length of service with the level of work fatigue among workers in HAR 1 and HAR 2 at the PLN Nusantara Power UP Belawan power plant. This study used a quantitative descriptive method with purposive sampling of 30 workers in the maintenance division. Data collection used the Subjective Self Rating Test questionnaire from the IFRC. The relationship between age and length of service and fatigue levels was analyzed using the Chi-Square test. The results showed that most workers experienced moderate fatigue levels (70%), while the rest experienced low fatigue levels (30%). The most dominant physical fatigue symptoms were increased frequency of drinking (score 90), back pain (score 67), and whole body fatigue (score 65). Statistical analysis showed that there was no significant relationship between age (p = 0.898) and length of service (p = 0.338) and work fatigue levels. Work fatigue among maintenance workers was more influenced by work environment factors and physical workload than by individual factors such as age and length of service.